High levels of biological activity of Cry1Ac protein expressed on MON 87701 × MON 89788 soybean against Heliothis virescens (Lepidoptera:Noctuidae). Issue 4 (14th June 2013) - Bernardi, Oderlei; Dourado, Patrick M; Carvalho, Renato A; Martinelli, Samuel; Berger, Geraldo U; Head, Graham P; Omoto, Celso
Abstract Background Genetically modified MON 87701 × MON 89788 soybean (Glycine max) that expresses the Cry1Ac and EPSP‐synthase proteins is a new Integrated Pest Management (IPM) tool for controlling Heliothis virescens in Brazil. To Support Insect Resistance Management (IRM) programs and understand the value of this event for IPM, we conducted laboratory and field studies to assess the biological activity of Cry1Ac protein expressed on Bt soybean against this insect pest. Results Heliothis virescens was highly susceptible to purified Cry1Ac protein [LC50 (FL 95%) = 0.026 (0.021–0.033) µg Cry1Ac mL–1 diet]. In bioassays with freeze‐dried MON 87701 × MON 89788 soybean tissue diluted 25 times in an artificial diet, there was 100% mortality of H. virescens. In bioassays with leaf disc, young trifoliate, flower buds, pods and high artificial infestation under greenhouse condition, MON 87701 × MON 89788 soybean showed a high level of control against H. virescens. Moreover, larvae from first through fifth instar were highly susceptible to MON 87701 × MON 89788 soybean. Conclusions The MON 87701 × MON 89788 soybean provides an effective alternative in controlling Heliothis virescens and complies with the concept of high‐dose for IRM programs. © 2013 Society of Chemical Industry